2001
DOI: 10.1161/01.cir.103.15.1999
|View full text |Cite
|
Sign up to set email alerts
|

Index Matching to Improve Optical Coherence Tomography Imaging Through Blood

Abstract: Background-Most myocardial infarctions are caused by the rupture of small rather than large plaques in the arteries of the heart that are beyond the detection limit of current technologies. Methods and Results-Recently, optical coherence tomography (OCT) has demonstrated considerable potential as a method for high-resolution assessment of vulnerable plaque. However, intravascular OCT imaging is complicated by the need to remove blood from the imaging field because blood results in substantial signal attenuatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
90
0
3

Year Published

2002
2002
2014
2014

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 131 publications
(96 citation statements)
references
References 22 publications
2
90
0
3
Order By: Relevance
“…First patient studies indicate the general safety of this method [197,198]. Nevertheless, research continues to eliminate the risk of ischemia completely, for instance by matching the refractive index of the blood serum with that of the red blood cells [199] or by using oxygen-carrying flushing liquids [200,201]. An important step was the introduction of high-speed FD-OCT systems, since it enabled the acquisition of large sampling volumes during relatively short flushing periods [36,195].…”
Section: Cardiologymentioning
confidence: 99%
“…First patient studies indicate the general safety of this method [197,198]. Nevertheless, research continues to eliminate the risk of ischemia completely, for instance by matching the refractive index of the blood serum with that of the red blood cells [199] or by using oxygen-carrying flushing liquids [200,201]. An important step was the introduction of high-speed FD-OCT systems, since it enabled the acquisition of large sampling volumes during relatively short flushing periods [36,195].…”
Section: Cardiologymentioning
confidence: 99%
“…Dies wird vermutlich durch die starken Streueigenschaften des Blutes [18] verursacht, welche die Eindringtiefe deutlich verringert. Die scheinbaren Rückstreusignale vom Zentrum der murinen Arterie können durch Mehrfachstreuung hervorgerufen worden sein und liefern damit keine realen Phasenbzw.…”
Section: Diskussionunclassified
“…Moreover, we have demonstrated that OCT cannot usually penetrate blood because of the high scattering caused by the difference in refractive index between serum and the cytoplasm of red blood cells (refractive index mismatch also causes the high scattering between lipidbased and water-based tissue). 3 By increasing the refractive index of serum, we have made blood almost transparent, thereby eliminating scattering. 3 This point is critical to interpreting plaque images, because the pronounced mismatch produced by small lipid collections and calcium clusters (but not macrophages) leads to high scattering, diffuse borders, and rapid attenuation.…”
mentioning
confidence: 99%
“…3 By increasing the refractive index of serum, we have made blood almost transparent, thereby eliminating scattering. 3 This point is critical to interpreting plaque images, because the pronounced mismatch produced by small lipid collections and calcium clusters (but not macrophages) leads to high scattering, diffuse borders, and rapid attenuation. Techniques exist, such as the use of a parallel continuous wave ultrasound beam or elastography, to overcome these effects.…”
mentioning
confidence: 99%